IMOBILISASI ENZIM LIPASE PADA PADATAN PENDUKUNG ZEOLIT ALAM - Fandhi Adi Wardoyo; Aprilia Indra Kartika (Universitas Muhammadiyah Semarang, 2017)
Lipase is one kind of enzyme that widely use. Lipase has a great catalytic power, but easily influenced by environments and difficult to separate at the ends of the reaction, so it can not be re-used. Based on that, one solution to overcome that problem is through the enzyme immobilization. Pancreaticlipase was immobilized by absorption method in zeolit as solid support. The aim of this reseacrh is to determine the optimum pH of lipase solubility. The activity of immobilized lipase was tested through the hydrolysis reaction of palm oil. The optimum pH for enzyme dissolution was obtained at pH 6 .Pancreatic lipase and immobilized lipase on zeolite can produce free fatty acid as much as17,37% and 7,35% respectively.Keywords: lipase, immobilization, zeolit, absorption